ROL DE MADRE Y SISTEMA LABORAL ACTUAL: UNA DOBLE CONDICIÓN PARA LA MUJER (2016)
This paper aims, to determine the incidence of the current Labor System woman in role performance as a mother within the family, especially childcare. The object of study is reflective - interpretive, through which a constructive broad perspective, analytical, critical and presents; on women in the current labor system, and performance of role of mother. Is discussed at length the impact on the family, especially for children and the mother, the current labor policy, particularly on the performance and development of daily activities. The model of family and cultural transformation processes is defined by diversity, the family is no longer the core of society. The current working conditions, more specifically public policy in Colombia, do not allow women to have enough for the upbringing and education of children time, causing many social problems that children suffer at the stage of adolescence such as the drug abuse, unwanted pregnancies; alcoholism, eating disorders, armed groups, antisocial disorders, among others.